IGRZYSKA OLIMPIJSKIE W NAGŁÓWKACH ZAMKNIĘTE - Grochala, Beata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents newspaper headlines of articles discussing the participation of Polish athletes in Olympic games in the 1988-2016 period. The headlines were extracted from 3 sources: a general daily “Gazeta Wyborcza”, a specialized sports daily “Przegląd Sportowy” and a tabloid “Super Express”. The analysis allowed for two main conclusions: the interest in sports is on the rise (which is expressed by the increasing number of articles being devoted to the topic); however, the Olympics are to a large extend depicted as a show, not as a sports event. The image of the Olympic games in the media is dynamic and increasingly tabloidlike.